2014
DOI: 10.1002/zoo.21163
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns and fine‐scale resource partitioning in the gregarious Kihansi spray toad Nectophrynoides asperginis in captivity

Abstract: Understanding the behavior of species threatened with extinction is important for conservation planning and for solving problems facing species in captivity and the wild. We examined diurnal activity budgets and habitat use of the extinct in the wild Kihansi spray toad to provide insights into ongoing conservation initiatives for this species. Observations on eight target behaviors were made each morning and evening for 14 days, in two subpopulations at Kihansi and University of Dar es Salaam captive breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Temperatures cooler than 18°C result in lower activity levels even if humidity is above 80%. Rija et al (2014) obtained similar results in Kihansi spray toads ( Nectophrynoides asperginis ) after they compared activity levels at different times of day, temperatures and relative humidity. Equally, a study by Köhler et al (2011) concentrated on activity levels and optimal body temperatures for common frogs ( Rana temporaria ) and found that jump lengths peaked at an optimal temperature and shortened with a decrease in temperature.…”
Section: Discussionmentioning
confidence: 74%
“…Temperatures cooler than 18°C result in lower activity levels even if humidity is above 80%. Rija et al (2014) obtained similar results in Kihansi spray toads ( Nectophrynoides asperginis ) after they compared activity levels at different times of day, temperatures and relative humidity. Equally, a study by Köhler et al (2011) concentrated on activity levels and optimal body temperatures for common frogs ( Rana temporaria ) and found that jump lengths peaked at an optimal temperature and shortened with a decrease in temperature.…”
Section: Discussionmentioning
confidence: 74%
“…LULCC is aided by human activities such as infrastructure development and agriculture, which threaten species through habitat loss, fragmentation and destruction (Doe et al, 2022; Franco‐Belussi et al, 2020; Mmbaga et al, 2017; Ngongolo et al, 2020; Ngongolo & Mtoka, 2013; Sigala et al, 2022). It has also been reported that human‐induced LULCC triggers ecological changes that lead to a decrease in biodiversity and increased species loss (Franco‐Belussi et al, 2020; Rija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The KST was estimated to have 20,000 individuals at the time of its discovery (prior to dam construction; Nahonyo, 2019). Due to habitat dryness influenced by water diversion after dam construction, there was a decrease in the number of toads (Rija et al, 2011). Artificial sprinkler systems were created to mimic natural sprays, which led to a rise in toads in 2001 (Nahonyo, 2019; Rija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent bird assessment reported no signi cant changes in bird community structures between pre and post hydropower construction periods (Werema and Msuya 2019) suggesting that impacts were probably only associated with some species. Further, some amphibian species such as the critically endangered Kihansi spray toad was severed, led its declaration as extinct in the wild species by International Union for Conservation of Nature-IUCN (Rija et al 2010), although reintroduction of the species into the gorge is ongoing (Rija et al 2014). Also, some plant species such as Coffea kihansiensis and Cupea jonii, remain critically endangered or threatened as their habitats have not fully recovered following the habitat disturbance (Rija et al 2011;Vollesen 2000).…”
Section: Introductionmentioning
confidence: 99%